The Lasting Effect of Sex Ratio Imbalance on Marriage and Family: Evidence from World War II in Russia - Brainerd, Elizabeth (The Review of Economics and Statistics, 2017)
How does a shock to sex ratios affect marriage markets and fertility? I use the drastic change in sex ratios caused by World War II to identify the effects of unbalanced sex ratios on Russian women. Using unique archival data, the results indicate that male scarcity led to lower rates of marriage and fertility, higher nonmarital births, and reduced bargaining power within marriage for women most affected by war deaths. The impact of sex ratio imbalance on marriage and family persisted for years after the war's end and was likely magnified by policies that promoted nonmarital births and discouraged divorce.